A positive approach to management education: The relationship between academic PsyCap and student engagement. Issue 9 (10th October 2016) - Luthans, Kyle W.; Luthans, Brett C.; Palmer, Noel F.
Abstract : Purpose: The purpose of this paper is to examine the relationship between the positive psychological strengths of undergraduate business students, collectively known as positive psychological capital (PsyCap), and their levels of engagement. Design/methodology/approach: This study has a cross-sectional design in which students from two Midwestern universities were surveyed regarding their levels of PsyCap and levels of engagement in educationally sound activities. Item response theory (IRT) and hierarchical regression were used to test study hypotheses. The authors assessed measurement validity using confirmatory factor analyses in MPLUS 7.0 using four-category 2PL graded response models with a weighted least squares means and variance adjusted estimator. Hierarchical regression was used to control for alternative explanations of variance in assessing the effects of PsyCap on student engagement. Findings: Using measures of student engagement drawn from the National Survey of Student Engagement, the analysis indicated significant positive relationships between the academic PsyCap of 323 undergraduate business students and their levels of student-faculty engagement (SFE; r =0.30, p <0.01), community-based activities (CBA; r =0.28, p <0.01), and transformational learning opportunities (TLO; r =0.19, p <0.01). A series of hierarchical regressions also indicated that PsyCap is a significant predictor of student engagement as assessed against SFE, CBA, and TLO. Research limitations/implications: The findings from this study suggest that further research examining the relationship between PsyCap development and student engagement could have significant implications for management educators. The positive associations found between these key variables could be utilized by management educators to implement novel and effective teaching interventions for developing the PsyCap of their students and, ultimately, increase their students' levels of engagement. Originality/value: Although extant research has demonstrated connections between positive psychological constructs (i.e. hope, self-efficacy, resilience, optimism) and student engagement, this is the first study to take a holistic view of developable, positive psychological capacities, collectively assessed as PsyCap, and examine the potential impact on three recognized dimensions of student engagement.